(2-Carboxyethyl) dimethylsulfonium bromide supplementation in non-fish meal diets for on-growing grass carp (Ctenopharyngodon idella): Beneficial effects on immune function of the immune organs via modulation of NF-κB and TOR signalling pathway. Issue 107 (December 2020) - Wu, Pei; Liu, Xing-Wei; Feng, Lin; Jiang, Wei-Dan; Kuang, Sheng-Yao; Tang, Ling; Shi, He-Qun; Zhou, Xiao-Qiu; Liu, Yang
Abstract: The immune function of immune organs is extremely crucial for maintaining organism health status, which ultimately affects fish growth. Our previous study has found that dietary supplementation of (2-carboxyethyl)dimethylsulfonium Bromide (Br-DMPT) in non-fish meal (NFM) diet could promote the growth of grass carp ( Ctenopharyngodon idella ), whereas the underlying reason or mechanism for this results is largely unclear. Herein, we further explored whether dietary supplementation of Br-DMPT promoted fish growth is connected with the enhanced immune function in the immune organs (the head kidney, spleen and skin). In this study, 540 fish (216.49 ± 0.29 g) were irregularly distributed to six groups with three replicates (30 fish replicate −1 ) and fed corresponding diets group containing a fish meal (FM) diet group and five different NFM diets supplemented with gradational Br-DMPT (0–520.0 mg/kg level) group for 60 days. After the 60-days feeding trial, 8 fish from each replicate were selected and then conducted a challenge test with A. hydrophila for 14 days. Our results indicated that in the NFM diets, appropriate Br-DMPT: (1) significantly decreased the morbidity of skin haemorrhage and lesion after A. hydrophila infection ( P < 0.05) . (2) significantly improved the innate and adaptive immune components (lysozyme, complement 3, immunoglobulin M and antibacterial peptides et al.) ( P < 0.05). (3) increased the gene expressions of main anti-inflammatory cytokines partially by referring to TOR signalling pathway, and decreased the gene expressions of main pro-inflammatory cytokines partially by referring to NF-kB signalling pathway ( P < 0.05). Strikingly, no statistical difference could be found in the most of above immune parameters between 260.0 mg/kg Br-DMPT diet group and FM diet group ( P > 0.05). Taken together, in non-fish meal diet, appropriate supplementation of Br-DMPT could improve the disease resistance capacity, non-specific immunity and ameliorate inflammation, and simultaneously could mitigate these adverse effects induced by the non-fish meal diet in fish immune organs. Moreover, this study may be helpful to decipher the underlying mechanisms of how Br-DMPT promote fish growth by immune organs and also provide scientific theoretical evidence for the future application of Br-DMPT as a new immunopotentiator in aquaculture industry. Highlights: 1、 Appropriate Br-DMPT supplementation enhanced skin disease resistance of fish. 2、 Appropriate Br-DMPT supplementation improved non-specific immunity of immune organs in fish. 3、 Appropriate Br-DMPT supplementation alleviated inﬂammation response involving cytokines of immune organs in fish. 4、 Appropriate Br-DMPT supplementation modulated NF-κB and TOR signalling in fish immune organs.